REPRODUCTIVE CHARACTERISTICS OF INDONESIA MAHSEER (Tor tambroides, Bleeker, 1854), IN TWO DIFFERENT RIVERS IN WESTERN SUMATERA - Arif Wibowo; Siswanta Kaban (Research Center for Fisheries, 2014)
The reproductive characteristics of mahseer, Tor. tambroides, were studied in Manna River and Batang Tarusan River, which are located on each side of Western Sumatera River. The reproductive period of T. tambroides is largely consistent with that described for the species in other areas, however monthly variations in the extent and timing of peak spawning are recorded. The analysis of the sex ratio indicates an increase in the percentage of females with size, more marked in largest sizes. Seasonal patterns in the occurrences of spawning showed that the spawning season in Manna River lasted was similar with that in Batang Tarusan River, although a second prominent increase of GSI was observed in April and September in Manna River, meanwhile the GSI of Batang Tarusan River fish were below 2 without an apparent variation. L50s of Manna River and Batang Tarusan River mahseer were estimated as 24.5 cm and 20.66 cm, respectively, indicating a high variability in size at first maturity of the mahseer population. Our study provides some important information on the reproductive biology of T. tambroides that will be helpful in similar studies and contributed to fisheries management of this species.